Exploring the Implementation of Cooperative Learning in EFL Classrooms: A Comparative Multiple Case Study in Public and Islamic Boarding Schools - Dhea Syahzana Sahreebanu; Sari Karmina; Nur Hayati (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This multiple case study examines the enactment of Cooperative Learning (CL) in English as a Foreign Language (EFL) classrooms at SMPN 1 Turen and MTsN 1 Malang. Situated within two contrasting educational ecosystems public schooling and Islamic boarding education this research explores how English teachers operationalize Cooperative Learning principles, how strategies are adapted across contexts, and how institutional norms and cultural values mediate pedagogical practice.Adopting a qualitative multiple case study design, data were generated through classroom observations, semi-structured interviews, and document analysis. The findings indicate that although both institutions implement foundational elements of Cooperative Learning positive interdependence, individual accountability, promotive interaction, and group processing their pedagogical enactment is contextually negotiated. In the public school context, CL is primarily aligned with curriculum-driven objectives, competency standards, and measurable academic outcomes. Meanwhile, in the Islamic boarding school, Cooperative Learning is deeply interwoven with religious ethos, collective discipline, moral formation, and communal identity, resulting in a more value-embedded instructional model.The study further reveals that institutional culture functions not merely as a background variable but as a transformative force shaping classroom interaction, authority patterns, student participation, and collaborative norms. Differences in organizational structure, leadership orientation, and educational philosophy significantly influence how collaboration is structured and sustained. Despite these variations, Cooperative Learning in both settings contributes to enhanced communicative competence, learner autonomy, social cohesion, and critical engagement.Conceptually, this research advances the understanding of Cooperative Learning as a culturally adaptive and context-responsive pedagogical framework rather than a universal procedural model. In the evolving landscape of 21st-century education marked by globalization, digital transformation, and the demand for collaborative intelligence contextualized Cooperative Learning emerges as a strategic pathway toward future-oriented, inclusive, and culturally grounded EFL instruction.